Successful use of radiotransmitters in tracking male tree wētā Hemideina crassidens (Orthoptera: Tettigonioidea: Anostostomatidae). Issue 1 (2nd January 2018) - Gwynne, Darryl T.; Kelly, Clint D.
ABSTRACT: Radiotransmitters have been used successfully to track and recapture giant wētā ( Deinacrida species) in part to assess mating success. We report the successful use of very light transmitters (0.2 g) to track male Wellington tree wētā, Hemideina crassidens, over several nights to daytime refuges in burrows and tree galleries. Male Hemideina species sport lengthy mandibles used as weapons in fights with rivals over groups of females living in gallery refuges. Consistent with previous studies showing that males with the longest mandibles cohabit with the largest groups of females, our two largest radio-tagged males were the only ones relocated with adult females.